Analysis of Compliance Companies in Paying BPJS Employment Contributions - Nasikhin Nasikhin; Cantika Firghotul Khasanah; Nur Salim; Muhammad Randy (STAIN Bengkalis, 2022)
This study aims to determine the level of compliance of companies in the Semarang city in paying BPJS Employment contributions and the factors that influence it. By using the percentage analysis model of Arikunto's qualitative conclusion technique which is aligned with the empirical legal approach of das sein, data is obtained that as many as 179,287 companies in Semarang City, 11,013 of them (6.1%) have complied with registering their workers into the BPJS Employment program. Meanwhile, companies that have complied in paying BPJS Employment contributions on time are 7,603 companies (64.1%). So it can be concluded that the level of compliance of companies in the city of Semarang in paying BPJS Employment contributions is high. However, the compliance level of BPJS Employment participation by companies in the city of Semarang is still very low. So that most of the workers in the city of Semarang are still not protected by their social security rights. As for the factors that affect compliance, namely, (1) There is a perception that employees will get social security, (2) There is an expectation that it will be easier to administer permits, and (3) So that they are not subject to sanctions. The factors that influence non-compliance are, (1) Lack of knowledge of the procedures for payment of contributions, (2) Unsupportive attitude towards policies, and (3) Stability of the company's financial condition which is declining.